Comparison of repetitive peripheral magnetic stimulation (rPMS) and sham-rPMS with supervised exercise on pain and function in knee osteoarthritis patients –protocol for randomized sham-controlled trial - P Madhuripu; Ajay Kumar; S Rajasheker; Prem Venkatesan (Journal of Education and Health Promotion)
BACKGROUND: Knee Osteoarthritis (KOA) is a degenerative joint condition that impairs patient’s quality of life and work productivity. Pharmacological management has been found to provide short-term symptomatic relief with adverse effects, whereas physical therapy has been recommended by guidelines as a prime treatment approach. The objective is to evaluate the effectiveness of repetitive peripheral magnetic stimulation (rPMS) in the treatment of KOA. MATERIALS AND METHODS: A sham-randomized controlled trial will be conducted in a physiotherapy outpatient department with 74 participants aged 45–65 with KOA. Participants will be randomized into two groups: Group A will receive rPMS and supervised exercise, while Group B will receive sham-rPMS and supervised exercise for 6 weeks. The outcomes Assessments will occur at baseline, 3 weeks, 6 weeks, and follow-up at 3 and 6 months. Statistical analysis will involve parametric or nonparametric tests based on data normality. Descriptive statistics will use means ± standard deviations or medians with 95% confidence intervals. Repeated measures ANOVA or Friedman’s test will analyze within-group differences, with post hoc tests for significant findings. Between-group comparisons will use unpaired t-tests or Mann-Whitney U tests, with effect sizes calculated after 6 weeks. A P value < 0.05 will be considered significant. RESULTS: The results will be reported using 95% confidence intervals to indicate the precision of the estimates and P values (with a significance threshold of <0.05) to assess the statistical significance of the findings. CONCLUSIONS: This is the first comprehensive sham-randomized controlled trial evaluating the true individual impact of rPMS in the treatment of OAK.